Manufacturing systems analysis of assembly manufacturing to improve performance - Goh, Diye (2014)
Variability is the greatest enemy of a manufacturing system; it causes unstable performances and varies the productivity of the manufacturing system. This report introduces to the reader about reducing variability to improve the performance of a manufacturing assembly cell. Other methods to improve performance of a manufacturing cell includes improving machine’s process time, improving standard work of operators and other ergonomics factors will be included in the project.